(untitled) (Law, State and Telecommunications Review, 2022)
[Purpose] The purpose of article is devoted to the study of the specifics of legal regulation, use and development of Artificial Intelligence (AI) and related issues of respect for fundamental human rights in modern Ukraine and the EU. [Methodology] The normative bases of legal regulation of relations in the field of AI are considered. One of the methods, used in this article, is establishment of such general rules for the use of AI that could not violate fundamental human rights. [Practical Implications] The practical significance lies in establishment that the use of AI is a multi-vector phenomenon that affects all spheres of human life and can violate various groups of rights [Findings] It was concluded that in order to regulate the use of AI, states need to pay attention to and take into account the Recommendations on AI developed by the European Commission and find a compromise approach to the use of AI, which provides for respect for fundamental human rights.